And Other Deaths Have Followed … (with Mouloud Feraoun). Issue 2 (4th May 2019) - Desjarlais, Robert
ABSTRACT: This essay, written in a journal-like format, attends to the journal written by Algerian writer Mouloud Feraoun from November 1955 to March 1962, during Algeria's war of independence against France, and published in France in 1962 with the title Journal 1955–1962 . In giving thought to the themes conveyed in the journal, from the devastating effects of the war on people's lives in Algeria to implications of violence and death, the essay speaks to recurrent dynamics of violence and subjection in the contemporary world, and the lasting significance of Mouloud Feraoun's writings on life, death, violence, colonialism, as well as the act of testimonial writing.